Institutional Ownership, Managerial Ownership, Audit Committee and Sales Growth Against Financial Distress during the Covid-19 Pandemic Period in Conventional Banking Sector Companies on the IDX 2018-2021: Kepemilikan Institusional, Kepemilikan Manajerial, Komite Audit dan Sales Growth Terhadap Financial Distress di Masa Pandemi Covid-19 pada Perusahaan Sektor Perbankan Konvensional di BEI 2018-2021 - Rahmawati, Regita Tri; Qudus, Nihlatul (Universitas Muhammadiyah Sidoarjo, 2023)
Conventional banking plays an important role in people's lives with the Covid-19 pandemic as a new challenge for companies engaged in the banking sector. “This study aims to examine the effect of institutional ownership, managerial ownership, audit committee and sales growth on financial distress during the Covid-19 pandemic”. In this study using quantitative techniques through SPSS data processing tools, sampling based on criteria or purposive sampling so that there were 19 companies that were taken as research samples based on 3-year reports so that a sample of 76 financial statements were selected and contained in predetermined criteria so that calculated based on the tabulation of the data obtained. According to the results of the study, it was found that institutional ownership has an effect on financial distress, managerial ownership has an effect on financial distress, the audit committee has an effect on financial distress, sales growth has no effect on financial distress. In this research, the result of the influence of determination is 66.8%